Public Accounts Committee on Planning Process and Monitoring Mechanism in Irrigation Projects relating to Ministry of Planning (Planning Commission) - Planning Commission (Planning Commission, 1993)
The Public Accounts Committee (PAC) examined the planning and monitoring of irrigation projects in India, highlighting significant issues related to inefficiencies and delays. The report underscores that the irrigation sector is crucial for agriculture, which supports the country's economy. The committee concludes that for effective irrigation management, a systematic and structured planning process must be in place, ensuring that accountability, timely decision-making, and resource allocation are improved significantly. The hope is for more sustainable development in irrigation, which is vital for food production and the economy.
Planning Commission
Planning Commission
Keywords: Deficiencies in Project Management; Shortfalls in Targets; Improving Execution; Commission Oversight; Need for Higher Prioritization; Maximizing Resource Utilization; Planning Board Response; Land Acquisition Issues; Master Planning for Irrigation; Improving Investigation Machinery; Community Involvement